MANAGEMENT OF GLYPHOSATE-RESISTANT HAIRY FLEABANE AND CONTRIBUTION OF THE PHYSIOLOGICAL POTENTIAL OF SEEDS TO RESISTANCE - Kaspary, Tiago Edu (2021)
Hairy fleabane (Conyza bonariensis L.) is a major weed of the conventional crop systems. Therefore, the objectives of the present study were to assess the responses of glyphosate-susceptible (S) and -resistant (R) C. bonariensis at various developmental stages and evaluate the physiological potential of seeds to propose alternative herbicides for the control of this weed. Two experiments were performed in replicates. The first experiment was performed in a greenhouse, arranged in a 2 × 3 × 10 factorial design. Specifically, two hairy fleabane biotypes (S and R) at different developmental stages (I, II, and III) were subjected to various treatments (glyphosate, chlorimuron-ethyl, metsulfuron-methyl, diclosulam, ammonium glufosinate, paraquat, paraquat+diuron, diquat, 2,4-D, and control). Percentage control was evaluated at 7, 14, 21, and 28 days after the application of the treatments (DAT), and shoot dry mass (SDM) was measured at 28 DAT. The second experiment was performed in a laboratory to evaluate the physiological potential of seeds based on the weight of 1000 seeds (TSW); shoot length (SL), radicle length (RL), total length (TL), fresh seedling mass (FSM), dry seedling mass (DSM), accelerated aging (AA) and cold test (CT), and germination (G) in response to cold and accelerated aging. The alternative herbicides tested effectively controlled biotype R up to the stage-I. Seeds of biotype R showed higher physiological potential in terms of all analyzed variables and exhibited greater tolerance to adverse conditions during seedling establishment. Therefore, strategies for the management of glyphosate-resistant hairy fleabane should aim at preventing new seed production.